The effect of silymarin on liver injury induced by Thioacetamide in rats - Kabiri Najmeh; Ahangar-Darabi Mahboobeh; Setorki Mahbubeh; Rafieian-kopaei Mahmoud (Shahrekord University of Medical Sciences, 2013)
Introduction: In this study the protective effects of Silymarin was investigated against thioacetamide (TAA) induced hepatotoxicity in rat. Methods: In an experimental study 24 male Wistar rats were designated in four equal groups as follows: Control group, the group treated with thioacetamide (TAA), Silymarin (400 mg/kg for 3 weeks) + TAA (400 mg/kg), TAA (400 mg/kg) + Silymarin (400 mg/kg for 3 weeks). The levels of serum aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP) lactate dehydrogenase (LDH) and total bilirubin were measured to assess the hepatotoxicity and hepatoprotection. Results: TAA significantly increased AST, ALT, ALP, LDH and bilirubin. Treatment by Silymarin caused a significant reduction in serum levels of AST, ALT, ALP, LDH and bilirubin contents. Conclusion: The results indicate a protective effect for Silymarin against thioacetamide induced hepatotoxicity which might be due to its ability to block the bioactivity of thioacetamide.